2021
DOI: 10.3390/f13010031
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Guttation on the Growth of Bamboo Shoots

Abstract: Guttation is the process of exudating droplets from the tips, edges, and adaxial and abaxial surfaces of the undamaged leaves. Guttation is a natural and spontaneous biological phenomenon that occurs in a wide variety of plants. Despite its generally positive effect on plant growth, many aspects of this cryptic process are unknown. In this study, the guttation phenomenon characteristic of bamboo shoots and the anatomical feature of these and culm sheaths were systematically observed. In addition, the water tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Additionally, the upper part of bamboo culm sheaths (s21-s31) was purplish-brown and densely covered with brown spines, whereas the lower part (s1-s10) contained scattered purple spots. Zheng et al (2022) observed numerous vascular bundles in the lower part of culm sheaths, where a greater number of xylem ducts were apparent in a vascular bundle and their cross-sectional area exceeded that of the phloem. This suggested that lower parts of the culm sheaths (s1-s10) exhibit a high capacity for water transport.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, the upper part of bamboo culm sheaths (s21-s31) was purplish-brown and densely covered with brown spines, whereas the lower part (s1-s10) contained scattered purple spots. Zheng et al (2022) observed numerous vascular bundles in the lower part of culm sheaths, where a greater number of xylem ducts were apparent in a vascular bundle and their cross-sectional area exceeded that of the phloem. This suggested that lower parts of the culm sheaths (s1-s10) exhibit a high capacity for water transport.…”
Section: Discussionmentioning
confidence: 92%
“…This study found that the pulp cavity of the bamboo shoots was unable to transport water (Figure 7A), and the vascular bundle adjacent to the pulp cavity of the bamboo wall served as the primary pathway for water transport (Figures 7B-D). Staining was also observed in the ducts of the bamboo nodal diaphragm (Figure 7D), Indicating that these interconnecting ducts played a crucial role in facilitating an efficient water-transport system in bamboo shoots (Zheng et al, 2022).…”
Section: Water Transportation Pathway In Bamboo Shoots During the Rap...mentioning
confidence: 85%
“…The bamboo root pressure exhibited circadian rhythms, with negative pressure in the daytime and positive pressure at night (Fig. 1a), and the root pressure fluctuation showed similar variation patterns with guttation rhythm (Zheng et al ., 2021). Importantly, we discovered a sharp upward trend in root pressure during the period of 18:00 to 21:00, coinciding with the fastest growth rate of bamboo shoots (Cheng et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The catabolism of starch and soluble sugars was significantly increased in the spring shoots of P. edulis [34]. The culm sheath uses water as a medium to transport organic acids, sugars, and other compounds to the internodes for the growth of P. edulis shoots [35]. Wang et al [36] found that sugar content was high in the fast elongation and mature internodes of Fargesia yunnanensis, implying that the elongation of bamboo internodes requires a large amount of sugar.…”
Section: Introductionmentioning
confidence: 99%